2013
DOI: 10.1002/j.2333-8504.2013.tb02342.x
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATING THE VALUE OF SECTION SCORES FOR THE TOEFL iBT® TEST

Abstract: This study investigates the value of reporting the reading, listening, speaking, and writing section scores for the TOEFL iBT ® test, focusing on 4 related aspects of the psychometric quality of the TOEFL iBT section scores: reliability of the section scores, dimensionality of the test, presence of distinct score profiles, and the section scores' generalizability for norm-referenced decisions as well as the dependability of criterion-referenced decisions for international student admission.Four operational TOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
(85 reference statements)
2
15
0
Order By: Relevance
“…This comparison showed that the correlated four-factor model representing the four language modalities of reading, listening, speaking, and writing best accounted for the underlying latent factor structure of the TOEFL iBT test. This result is consistent with a recent investigation by Sawaki and Sinharay (2013) into the factor structure of the TOEFL iBT test. However, these findings are different from that of Sawaki et al (2008), who concluded that the higher-order factor model with a higher-order general factor representing ESL/EFL and four first-order factors for reading, listening, speaking, and writing represented the factor structure of the TOEFL iBT test.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This comparison showed that the correlated four-factor model representing the four language modalities of reading, listening, speaking, and writing best accounted for the underlying latent factor structure of the TOEFL iBT test. This result is consistent with a recent investigation by Sawaki and Sinharay (2013) into the factor structure of the TOEFL iBT test. However, these findings are different from that of Sawaki et al (2008), who concluded that the higher-order factor model with a higher-order general factor representing ESL/EFL and four first-order factors for reading, listening, speaking, and writing represented the factor structure of the TOEFL iBT test.…”
Section: Discussionsupporting
confidence: 93%
“…In the first step, an item-level CFA was used to evaluate several competing models representing the factor structure of the TOEFL iBT test. These models used in this study were similar to those studied in previous CFA analyses of the TOEFL iBT test (Gu, 2014;Sawaki & Sinharay, 2013;Sawaki et al, 2008;Stricker & Rock, 2008). Specifically, the following six factor structures, as described in Sawaki et al (2008), with the exception of 4a, were evaluated and are diagramed in Appendix.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the correlated four-factor model has been found to represent English-language proficiency of adult learners using the TOEFL iBT ® test (Manna & Yoo, 2015;Sawaki & Sinharay, 2013), despite the differences in target age groups and assessment instruments. However, unlike adult learners, for whom differential performance across the four latent constructs is not unexpected due to greater variation in background characteristics, the levels of proficiency across the latent constructs in the two groups of adolescent learners studied tended to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the general view among researchers is that L2 proficiency is complex and multidimensional in nature (Carroll, 1965;Harsch, 2014;Oller, 1983). As noted earlier, this view has been supported by a number of factor analytic studies that found that language ability comprises one or more components representing the four language skills (reading, listening, speaking, and writing) that may be distinct, closely related, or hierarchically related to a global ability (Bachman et al, 1995;Sawaki & Sinharay, 2013;Sawaki, Stricker, & Oranje, 2009).…”
mentioning
confidence: 83%